Analysis of Problem Solving Capabilities in Problem Based Learning Contextual Approaches Based on Metacognitive Awareness - Achsin, Muchammad Achsin; Kartono, Kartono; Wibawanto, Hari (Universitas Negeri Semarang, 2020)
The purpose of this study is to test the effectiveness of PBL contextual approaches to problem solving abilities, analyze the problem solving abilities that are subjected to PBL contextual approaches based on metacognitive awareness. The research method used is mixed methods with a concurrent embedded model. The population in this study were students of class VIII SMP N 1 Mejobo Kudus in the 2018/2019 school year. Data collection uses documentation, questionnaires, test results and interviews. Using the cluster random sampling technique, one experimental class and one control class were obtained. The results showed that PBL learning was an effective contextual approach to students' problem solving abilities. Students with high, moderate and low metacognitive awareness experience the same mathematical problem solving abilities. Students with high metacognitive awareness after learning are able to master all stages of problem solving. Students with metacognitive awareness are able to master the stage of understanding the problem and implementing the plan while the stage of making plans and checking back tends to be able. Students with low metacognitive awareness before learning are less able in all stages of improvement. After learning to be able to understand the problem, tend to be able to carry out plans, make plans and check again.